KEMAMPUAN METAKOGNISI SISWA DALAM MEMECAHKAN MASALAH SISTEM PERSAMAAN LINEAR TIGA VARIABEL PADA SISWA KELAS X SMA NEGERI 15 MAKASSAR - Varah Umay’ah Husain (Jurnal Education, 2025)
This study is a qualitative study that aims to determine students' metacognitive abilities in solving problems of three-variable linear equation systems in class X students of SMA Negeri 15 Makassar who were selected based on certain criteria with the snowball sampling technique. Data collection was carried out by giving problem-solving tests supported by interview data. Data validity testing used source triangulation. The results of the study showed that students with high and low mathematical abilities in solving problems of three-variable linear equation systems had metacognitive awareness and were aware of how to use a strategy, but only students with high abilities had metacognitive regulation and evaluation. This shows that in solving mathematical problems, students with high academic abilities involve three components of metacognition, namely awareness, regulation, and evaluation. Meanwhile, students with low academic abilities were only able to involve one component of metacognition, namely metacognitive awareness.